Genomic Strategy Identifies a Missense Mutation in WD-Repeat Domain 65 (WDR65) in an Individual With Van der Woude Syndrome - Rorick, Nicholas K.; Kinoshita, Akira; Weirather, Jason L.; Peyrard-Janvid, Myriam; Ferreira de Lima, Renata L. L.; Dunnwald, Martine; Shanske, Alan L.; Moretti-Ferreira, Danilo [UNESP]; Koillinen, Hannele; Kere, Juha; Mansilla, Maria A.; Murray, Jeffrey C.; et al. (Wiley-Blackwell, 2011)
Genetic variation in the transcription factor interferon regulatory factor 6 (IRF6) causes and contributes risk for oral clefting disorders. We hypothesized that genes regulated by IRF6 are also involved in oral clefting disorders. We used five criteria to identify potential IRF6 target genes; differential gene expression in skin taken from wild-type and Irf6-deficient murine embryos, localization to the Van der Woude syndrome 2 (VWS2) locus at 1p36-1p32, overlapping expression with Irf6, presence of a conserved predicted-binding site in the promoter region, and a mutant murine phenotype that was similar to the Irf6 mutant mouse. Previously, we observed altered expression for 573 genes; 13 were located in the murine region syntenic to the VWS2 locus. Two of these genes, Wdr65 and Stratifin, met 4 of 5 criteria. Wdr65 was a novel gene that encoded a predicted protein of 1,250 amino acids with two WD domains. As potential targets for Irf6 regulation, we hypothesized that disease-causing mutations will be found in WDR65 and Stratifin in individuals with VWS or VWS-like syndromes. We identified a potentially etiologic missense mutation in WDR65 in a person with VWS who does not have an exonic mutation in IRF6. The expression and mutation data were consistent with the hypothesis that WDR65 was a novel gene involved in oral clefting. (C) 2011 Wiley-Liss, Inc.
Keywords: cleft lip and palate; mutation; gene expression; syndrome; genomic; microvilli; WD domain; transcription factor